Etymologia ex silentio : Nganasanin äännehistoria ja kielikontaktit - Kaheinen, Kaisla (Helsingin yliopisto, 2023)
The current dissertation is a case study in historical linguistics, focusing on the genealogical position, sound history, and hitherto unetymologised lexicon of Nganasan, a language belonging to the Samoyed branch of the Uralic language family. It has been assumed that a large portion of Nganasan lexicon remaining without known etymology has been borrowed from an unknown language or languages of northern Siberia at the time when early Samoyed speakers started spreading to the North, and, in the process, linguistically assimilating preexisting populations. My dissertation applies the historical-comparative method of linguistics to the portion of Nganasan vocabulary without any known etymology, or with spread limited to the geographically northern Samoyed languages. In addition, I trace the historical developments of Nganasan phonology, based on which the genealogical position of Nganasan within the Samoyed branch can be determined. The main results of my work are the following: a detailed description of the historical development of the Nganasan sound system, a genealogical taxonomy of the Samoyed languages based mainly on phonological and morphophonological isoglosses, and a classification of the hitherto unetymologised portion of Nganasan lexicon with spread limited to the North. There is little support for the previous hypotheses, suggesting either a common proto language for the northern Samoyed languages, or exceptionally early splitting of Nganasan from the Proto-Samoyed linguistic unity. Based on this, lexemes with regular sound correspondences between northern Samoyed languages can be assumed to go back to Proto-Samoyed, even if their spread is limited. There are 210 such vocabulary items in my data. Additionally, there are lexemes with irregular correspondences between the northern Samoyed languages, which are either later borrowings from one Samoyed language to another, or parallel borrowings from an unkown source. There are 172 lexemes of this type in my data. Finally, there are 615 lexemes unique to ...